1982
DOI: 10.1159/000182512
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Fatigue in Dialysis Patients

Abstract: 137 patients on maintenance dialysis were studied. All but 2 patients were ambulatory, and all patients demonstrated good to normal strength on manual motor tests. With the exception of systemic lupus erythematosus, no correlation was found between primary diagnosis and patients’ fatigue ratings. Laboratory studies of hematocrit, BUN, creatinine, calcium, and phosphorus did not correlate with fatigue ratings for the majority of patients. Fatigue appeared more problematic for patients who had been dialyzing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 8 publications
6
49
1
1
Order By: Relevance
“…2 It has been shown that 50.6% to 58.3% of dialysis patients experience fatigue. 11,12,13 The results of the present study indicated that high levels of fatigue are experienced. Determining patients' level of fatigue and then ensuring that particular activities are planned for patients are clearly important responsibilities for medical professionals.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…2 It has been shown that 50.6% to 58.3% of dialysis patients experience fatigue. 11,12,13 The results of the present study indicated that high levels of fatigue are experienced. Determining patients' level of fatigue and then ensuring that particular activities are planned for patients are clearly important responsibilities for medical professionals.…”
Section: Discussionsupporting
confidence: 49%
“…At the same time, in a study by Cardenas and Kutner, a positive relationship was found between fatigue level and age. 11 The reason for this result is probably due to physiological changes that occur with age as well as psychosocial effects of a chronic illness on the individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last check we made on the validity of fatigue as a criterion for depression concerned the time of the day fatigue was most intense, because it has been found that many symptoms related to depression are strongest in the morning [5,7,26]. However, less than 8% of our patients reported that they were tired particularly in the morning.…”
Section: Discussionmentioning
confidence: 96%
“…More somatic manifestations of depression are not totally discarded, however. For instance, because many symptoms related to depression are most prevalent in the morning [5,7,26], the time of day when fatigue is worst can be considered relevant. In addition, if a somatic symptom is far more pronounced than can be expected on the basis of the somatic illness, this might be suspected to be related to depression.…”
Section: Introductionmentioning
confidence: 99%